Endocrine resistance in advanced breast cancer: current evidence and future directions. (November 2012) - Barrios, Carlos H; Fay, André P; Debiasi, Marcio; Werutsky, Gustavo
SUMMARY  Hormone receptor-positive breast cancer constitutes a heterogeneous group representing the majority (60–75%) of patients with the disease. Hormonal approaches interfering with receptor signaling represents an established treatment strategy with demonstrated efficacy and favorable toxicity profile. However, due to either primary or acquired resistance, metastatic hormone receptor-positive breast cancer remains incurable. Mechanisms of resistance are complex and still poorly understood. Estrogen receptor signaling interactions with critical growth factor pathways and various downstream kinases have been implicated. Available evidence recommends a sequential single-agent approach to advanced hormone receptor-positive disease as a preferred therapeutic alternative. Recent information suggests that rational mTOR inhibition modulates hormonal resistance. Further advances in this field will require analysis of biopsies from metastatic sites at the time of progression.